PENGARUH SENAM YOGA TERHADAP PERUBAHAN TEKANAN DARAH PADA PENDERITA HIPERTENSI DI WILAYAH KERJA PUSKESMAS PANDANWANGI KOTA MALANG - joko wiyono; Elinda Miftahur Rohma; Fiashriel Lundy (Poltekkes Kemenkes Malang, 2021)
Anesthetic effects after sectio cesarean surgery cause complications in the thermoregulation system, like post anesthesia shivering. Shivering can also cause surgical wound pain because there is a stretch in the surgical wound. The purpose of this study was to determine the relationship between post anesthesia shivering with pain intensity in post op sectio caesarea patients in recovery room Bangil District Hospital. This study uses a correlation study design with a cross-sectional approach. The number of samples was take 33 respondents with quota sampling techniques used observation sheet of post anesthesia shivering and pain intensity. Spearman test results obtained p-value 0,000 which means there is a relationship between post anesthesia shivering with pain intensity in post op sectio caesarea patients and the relationship between the two variables is very strong. The results of this study is most respondents felt degree 2 and 3 of post anesthesia shivering and felt moderate pain, there was a significant relationship when the degree of post anesthesia shivering increase, the pain intensity also increase. So it’s recommended to further researchers examine other variables such as duration of operation, room temperature, and type of anesthesia used.